Synthesis of Uniformly Excited Concentric Ring Arrays by the Strategy of Partial Density Tapering and the Algorithm of Differential Evolution - Xin-Kuan Wang; Gui-Bao Wang; Jianke Jia; Chao-Jun Huang (International Journal of Antennas and Propagation)
A new strategy of density tapering called the partial density tapering (PDT) accompanied with the algorithm of differential evolution (DE) is proposed to suppress the peak sidelobe level (PSL) of uniform excited concentric ring arrays (UECRA) with isotropic elements. Through performing the PDT, a sound starting solution for DE can be generated. Then, the ring filling factor (RFF) is introduced so that the optimization of the number of elements can be transformed into the optimization of RFFs within the tapered thresholds, and thereby the real coding can be directly used with respect to the consideration of parallel encoding strategy. Finally, the UECRA featuring improved PSL performance can be obtained by limited runs of conventional DE. Several numerical instances for UECRA, with aperture sizes ranging from small to large scale, confirmed the outperformance of the proposed method.